Cocksfood forage yield inoculated with PGPB bacteria - Solís-Oba, María Myrna; Aguilar-Benítez, Gisela; Castro-Rivera, Rigoberto; Villegas-Aparicio, Yuri; Castro-Ramos, Job Jonathan; Solís-Oba, Aida (Revista Mexicana de Ciencias Agrícolas, 2020)
The PGPB bacteria have beneficial effects on crop yields. The aim of the present study was to determine the effect of five plant growth promoting bacteria on yield, plant height, SPAD units and content of protein in cocksfood defoliated every five weeks in spring and summer, under greenhouse conditions. A completely random design was used, with factorial arrangement 5x2x2, being the experimental unit a pot with ten stems, with four repetitions. The bacteria evaluated were: Ewingella americana (digestate), Ewingella americana (Soil), Pseudomonas clororaphis, Bacillus toyonensis and Microbacterium oxidans; compared with each other, and with the positive (triple 17) and negative (soil without fertilization) controls. The highest values of dry matter yield in spring were recorded by E. americana (3.5 g DM pot), while in summer it was B. Toyonensis. The height values did not register differences (p> 0.05) in both epochs, the SPAD units only in the summer and E. americana registered the lowest values (1.8). The protein content evidenced that the controls were inferior to all the treatments that were inoculated. The evaluated bacteria recorded effects on all evaluated variables and were superior to inorganic fertilization and unfertilized soil.
Keywords: Bacillus toyonensis; Ewingella americana; Microbacterium oxidans and Pseudomonas clororaphis